2008
DOI: 10.3727/154427308788714821
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Recreational Boating Pressure in the Rottnest Island Reserve, Western Australia

Abstract: Rottnest Island, off Western Australia, is a popular holiday destination with 0.5 million visitors annually, of which 150,000 arrive by private vessel. Management of these vessels is difficult as few data are available on their visitation patterns and associated recreational activities. An observational survey was conducted to provide baseline data. It clearly indicated higher vessel numbers during summer and on public holidays with some mooring areas exceeding 100% occupancy during these periods. Scuba diving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…These studies show that more boats are observed at weekends and on bank holidays (e.g. National Day), during summer months and when the weather is sunny (Widmer and Underwood, 2004;Smallwood and Beckley, 2008;Dalton et al, 2010;Smallwood et al, 2011). All together these factors were found to partly explain intra-annual variations of recreational use.…”
Section: Introductionmentioning
confidence: 82%
“…These studies show that more boats are observed at weekends and on bank holidays (e.g. National Day), during summer months and when the weather is sunny (Widmer and Underwood, 2004;Smallwood and Beckley, 2008;Dalton et al, 2010;Smallwood et al, 2011). All together these factors were found to partly explain intra-annual variations of recreational use.…”
Section: Introductionmentioning
confidence: 82%
“…This approach was adapted from well-known roving creel techniques often used to survey recreational fishing (Pollock, Jones, and Brown 1994), and involves researchers travelling in a vehicle to vantage (observation) points situated along a pre-determined route throughout the study area where they undertake counts and/or interviews. Such surveys have been effective at measuring recreational use occurring at small, confined spatial scales such as islands (Smallwood and Beckley 2008) and coastal embayments (Widmer and Underwood 2004). Expanding this technique to a large (∼300 km long) study area required splitting Ningaloo Marine Park coastline into three survey routes, each of which covered about 100 km of coastline and could be completed in a single day ( Figure 1).…”
Section: Survey Design and Sampling Regimementioning
confidence: 99%
“…Rottnest Island is a popular tourism destination, with approximately half a million visitors per year, with 150,000 arriving by private vessel (Smallwood and Beckley, 2008). The RIA is committed to increasing the environmental, social, and economic sustainability of the Island through increasing the placement of renewable energy, increasing energy efficiency and actions to promote carbon sequestration through potential revegetation programs.…”
Section: Resultsmentioning
confidence: 99%